2016
DOI: 10.1103/physrevb.94.064423
|View full text |Cite
|
Sign up to set email alerts
|

Pulse and quench induced dynamical phase transition in a chiral multiferroic spin chain

Abstract: Quantum dynamics of magnetic order in a chiral multiferroic chain is studied. We consider two different scenarios: Ultrashort terahertz (THz) excitations or a sudden electric field quench. Performing analytical and numerical exact diagonalization calculations we trace the pulse induced spin dynamics and extract quantities that are relevant to quantum information processing. In particular, we analyze the dynamics of the system chirality, the von Neumann entropy, the pairwise and the many body entanglement. If t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 84 publications
0
25
0
Order By: Relevance
“…While the determination of Lee-Yang zeros here was based on calculations of the magnetization cumulants, it would be interesting to implement our method in an experiment by measuring the magnetization fluctuations in an Ising lattice of finite size. In addition, the method is not restricted to equilibrium problems only, but may equally well be applied to dynamical phase transitions in quantum many-body systems after a quench [25][26][27] or quantum phase transitions in the groundstate of an interacting quantum spin chain [58,59].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the determination of Lee-Yang zeros here was based on calculations of the magnetization cumulants, it would be interesting to implement our method in an experiment by measuring the magnetization fluctuations in an Ising lattice of finite size. In addition, the method is not restricted to equilibrium problems only, but may equally well be applied to dynamical phase transitions in quantum many-body systems after a quench [25][26][27] or quantum phase transitions in the groundstate of an interacting quantum spin chain [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…They could thereby explain the nonanalytic behavior of the free energy that develops in the thermodynamic limit and signals a phase transition. The Lee-Yang formalism has been applied to a variety of equilibrium problems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18], and it has been realized that the framework can also be used to understand nonequilibrium phase transitions [19][20][21][22][23][24], such as dynamical phase transitions in quantum systems after a quench [25][26][27] and space-time phase transitions in glass formers [28][29][30][31] and open quantum systems [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…Wave localization by disorder is a ubiquitous phenomenon widely discussed for quantum [1] and for classical waves [2][3][4] and can be interpreted by scattering and interferences without involving many-body interactions. Correlated quantum systems may exhibit disorder-induced many-body localization involving states with a high energy level density [5][6][7][8][9][10][11][12][13][14], as well as correlation-induced localized states, called quantum scars [15]. Scars in wave functions, meaning enhanced localization of the probability density for states in the high energy level density part of the spectrum, were first discussed for non-interacting systems [16][17][18][19][20] and interpreted by analyzing the classical orbits of an electron or waves in various confinements such as chaotic billiards [16][17][18][19][20][21][22][23][24][25][26]; for a discussion, we refer to the book by Heller [27].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decades, the ideas of Lee and Yang have developed into a powerful theoretical tool in statistical physics 15,16 with applications to diverse problems ranging from protein folding 17,18 over percolation 19,20 and complex networks 21,22 to Bose-Einstein condensation. [23][24][25][26] Further extensions include the use of Lee-Yang zeros to characterize phase transitions in non-equilibrium systems, 15,16,27 quenched quantum systems, 28,29 and glass formers. [30][31][32][33] In addition, a number of experiments have shown that Lee-Yang zeros are not just a theoretical concept; they can also be experimentally determined.…”
Section: Introductionmentioning
confidence: 99%